In the Pre-eclamp sia and Normotensive Patient- Lipid Profile Study (Medicine Today, 2017)
Pre-eclampsia is associated with substantial risks for the fetus and mother. Disorders of lipoprotein metabolism are reported to be a major cause of hypertension and proteinuria in pre-eclampsia. This was a cross-sectional comparative study carried out in the Department of Obstetrics and Gynecology, Sylhet, M.A.G Osmani Medical College Hospital, Sylhet during December 2013 to May 2014. 50 pre-eclampsia and 50 normotensive pregnant women's serum lipid profile were selected according to inclusion and exclusion criteria. Fasting lipid profile was measured after 10-12 hours overnight fasting. The mean age (25.12 # 3.98 years vs 24.94 # 3.90 years; p=0.820), gestational age (36.80 # 0.70 weeks vs 36.9 # 1.1 weeks ; p=0.144), and BMI (21.43 # 2.09kg/M2 vs 22.02 # 1.73kg/M2, p=0.131) were statistically similar in both pre-eclamptic women and the control pregnant women. SBP (163.70 #11.24mm of Hg vs 115.10 # 9.39mm of Hg; p